Na4P2O7-Modified Biochar Derived from Sewage Sludge: Effective Cu(II)-Adsorption Removal from Aqueous Solution - Liangqian Fan; Xianda Wang; Jiaxin Miao; Qin Liu; Jie Cai; Xiaochan An; Fenghui Chen; Lin Cheng; Wei Chen; Hongbing Luo; Xiaoxiao Zhang; Ke Zhang; et al. (Adsorption Science & Technology)
With the rapid development of industrialization, the amount of copper-containing wastewater is increasing, thereby posing a threat to the aquatic ecological environment and human health. Sludge biochar has received extensive concern in recent years due to its advantages of low cost and sustainability for the treatment of heavy-metal-containing wastewater. However, the heavy-metal-adsorption capacity of sludge biochar is limited. This study prepared a sodium pyrophosphate- (Na4P2O7-) modified municipal sludge-based biochar (SP-SBC) and evaluated its adsorption performance for Cu(II). Results showed that SP-SBC had higher yield, ash content, pH, Na and P content, and surface roughness than original sewage sludge biochar (SBC). The Cu(II)-adsorption capacity of SP-SBC was 4.55 times than that of SBC at room temperature. For Cu(II) adsorption by SP-SBC, the kinetics and isotherms conformed to the pseudo-second-order model and the Langmuir–Freundlich model, respectively. The maximum adsorption capacity of SP-SBC was 38.49 mg·g−1 at 35°C. Cu(II) adsorption by SP-SBC primarily involved ion exchange, electrostatic attraction, and precipitation. The desired adsorption performance for Cu(II) in the fixed-bed column experiment indicated that SP-SBC can be reused and had good application potential to treat copper-containing wastewater. Overall, this study provided a desirable sorbent (SP-SBC) for Cu(II) removal, as well as a new simple chemical-modification method for SBC to enhance Cu(II)-adsorption capacity.